Importance of Strategic Management in Organizations of a Liberalized Country: The Case of Nepal - Karn, Niranjan Kumar (Academic Journal of Simara, 2026)
Since the early 1990s, Nepal’s transition from a state-controlled to a liberalized economy has intensified competition, drawn foreign investment, and exposed organizations to global standards and rapid change, rendering strategic management essential for survival and growth. This paper conceptualizes the value of strategic management in Nepal’s liberalized context, integrating theories such as Porter’s competitive strategy, the resource-based view, and dynamic capabilities with Nepal-specific economic data. Employing a qualitative, descriptive-analytical design, the study draws on secondary sources including books, journals, government reports, and company documents and illustrates applications through cases from Nepal’s banking (Nabil Bank), manufacturing (Chaudhary Group), and telecommunications (Ncell) sectors. Findings reveal that strategic management enables Nepalese firms to anticipate policy shifts, navigate competition and regulatory risks, develop unique capabilities, and achieve sustained performance via deliberate and emergent strategies. Implications for managers, policymakers, and educators are discussed, alongside avenues for empirical research.